2021
DOI: 10.1002/vms3.518
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Porcine circovirus 3 from captured wild boars in Korea

Abstract: Porcine circovirus 3 (PCV3) is a newly discovered ssDNA virus. The virus was first reported in pigs suffering from several clinical syndromes, including porcine dermatitis and nephropathy syndrome, reproductive disorders, respiratory disease and myocarditis. PCV3 was recently reported in wild boars with high prevalence as well. In this study, 266 wild boar anal swab, feces, nasal swab and whole blood samples were collected from three mainland provinces and one island province (Chungbuk, Gangwon, Gyeonggi, Jeju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In this study, positive rates of PCV2 between 2018 and 2019 were much higher (18% and 46.3% in lung and HLN, respectively). Other Korean research teams have demonstrated that positive rates of PCV3 in whole blood, serum, and nasal swabs (Dhandapani et al, 2021) and whole blood (Song et al, 2021) samples of wild boars were 5.6% and 0.01 %, respectively. Although we cannot rule out the possibility of other influences, these rapidly increasing positive rates of PCV3 in this study might be due to sample differences (Kixmöller et al, 2008;J.…”
Section: ) the Discrepancy Of The Target Cells Between Pcv2 And Pcv3mentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, positive rates of PCV2 between 2018 and 2019 were much higher (18% and 46.3% in lung and HLN, respectively). Other Korean research teams have demonstrated that positive rates of PCV3 in whole blood, serum, and nasal swabs (Dhandapani et al, 2021) and whole blood (Song et al, 2021) samples of wild boars were 5.6% and 0.01 %, respectively. Although we cannot rule out the possibility of other influences, these rapidly increasing positive rates of PCV3 in this study might be due to sample differences (Kixmöller et al, 2008;J.…”
Section: ) the Discrepancy Of The Target Cells Between Pcv2 And Pcv3mentioning
confidence: 99%
“…Wild boar (Sus scrofa) is a susceptible host and suspected to be an important reservoir of pathogens infecting commercial pigs and humans (Dhandapani et al, 2021;Prinz et al, 2019). PCV2 and PCV3…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Palinski et al [4] was the rst to discover PCV3 through metagenomic analysis in diseased sows with Porcine Dermatitis and Nephropathy Syndrome (PNDS) and in aborted foetuses. Since then, numerous reports detecting PCV3 have been published in many countries, including the United States, China, Brazil, Italy, South Korea, Thailand, Spain, Denmark, Germany, Sweden, and Poland, indicating the rapid global spread of the virus [5][6][7][8][9][10][11][12]. In addition to being detected in pigs, PCV3 has also been identi ed in canids and other mammalian species [13,14].…”
Section: Introductionmentioning
confidence: 99%